Multichannel mapping of fetal magnetocardiogram in an unshielded hospital setting - Brisinda, Donatella; Comani, Silvia; Meloni, Anna Maria; Alleva, Giovanna; Mantini, Dante; Fenici, Riccardo (Prenatal diagnosis, 2005)
Objectives To evaluate the feasibility of unshielded in‐hospital multichannel mapping of fetal magnetocardiogram (FMCG), with a 36‐channel system for standard adult magnetocardiographic (MCG) recordings, and its reliability according to the recommended standards for FMCG. Methods FMCG was ambulatory mapped with a 36‐channel MCG system, in six normal pregnancies at different gestational ages. MCG analysis included adaptive digital filtering of 50 Hz, signal averaging, reconstruction of magnetic field distribution (MFD) and source localization. Fixed Point Independent Component Analysis algorithm (FastICA) was used to reconstruct the FMCG, separating them from maternal contamination and noise. Results The quality of FMCG recorded after the 32nd gestational week and reconstructed with FastICA was close to FMCG obtained in shielded rooms, and good enough to measure cardiac intervals and heart rate variability parameters. In two cases, reconstruction of the MFD during the QRS allowed three‐dimensional localization of ventricular sources. Conclusions A first demonstration has been given that multichannel mapping of FMCG can be performed in unshielded clinical environments, with resolution good enough for contactless assessment of fetal cardiac electrophysiology. FastICA processing on unshielded FMCG, recorded after the 32nd week, provided beat‐to‐beat analysis and heart rate variability assessment. Further work is needed to improve signal reconstruction in early pregnancy. Copyright © 2005 John Wiley & Sons, Ltd.